One Piece Flag as Symbolic Communication in Indonesian Digital Discourse - Kamila Izzatun Nisa’; Reza Safitri (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines the One Piece flag controversy on X during Indonesia’s Independence Day period as a case of symbolic communication in digital public discourse. Rather than treating the debate merely as an anime fandom issue or viral digital expression, this article analyzes how Indonesian digital publics evaluated the legitimacy of a borrowed popular culture symbol in relation to national symbolism. Using a qualitative digital discourse design within a critical constructivist paradigm, the study analyzed 473 focused X posts selected from 1,596 crawled public posts and six semi-structured interviews with X users representing supportive, opposing, and conditional positions. Stuart Hall’s theory of representation and encoding/decoding was used as the main analytical framework, supported by the concepts of symbolic reappropriation and transcultural identity. The findings reveal three interpretive patterns. First, some users legitimized the One Piece flag by translating it into a language of public criticism, solidarity, and social anxiety. Second, some users delegitimized the symbol as foreign, fictional, mistimed, or improper within the Indonesian national symbolic space. Third, some users negotiated its legitimacy by accepting the flag only when it remained visually and symbolically subordinate to the Red-and-White flag. The study argues that the controversy reflects a platform-mediated process of symbolic legitimacy-making, where meaning is not only produced but also publicly tested, corrected, rejected, and limited through digital interaction. This article contributes to communication studies by showing how representation, civic expression, and national belonging are negotiated through popular culture symbols in digital public discourse.